Meningkatkan Kesadaran Masyarakat Tentang Kebutuhan Darah Melalui Pemeriksaan Golongan Darah Sistem ABO dan Rhesus - Gina Nafsa Mutmaina; Sugiah Sugiah; Mamay Mamay; Astari Nurisani; Muhamad Hadi Sulhan; Lia Mar’atiningsih; Meti Rizki Utari; Esa Risi Suazini (STIKes Ibnu Sina Ajibarang, 2024)
The national blood demand is estimated to reach around 5.5 million bags per year, while the available blood supply is only around 4.1 million bags. This results in a significant annual blood shortage, approximately 1.4 million bags. The root cause of the main problem of unmet blood needs lies in the lack of public awareness. Therefore, efforts are needed to increase public education and awareness about the importance of blood donation and the high demand for blood. Activities include counseling and blood type testing of the ABO and Rh systems using the slide test method. The examination results show that the most common blood type found in Lampegan Village is type O, while the least common is type B. Almost all of them have Rh-positive blood type, and Rh-negative was found in one resident. Knowing the exact blood type and adopting a healthy lifestyle can help someone become a blood donor. Blood type testing is a persuasive strategy to raise public awareness about the importance of blood types and the benefits of blood donation.